Kulturotwórczy i polityczny wymiar działalności edukacyjnej - Homa, Tomasz (Horyzonty Wychowania, 2017)
The reflection upon broadly understood education, its premisesand aims to be achieved, as well as the ways in which theyare specified, is the reflection upon all that society lives and feedson, and aims at. Therefore, it is also the reflection on how societycomprehends its common good and the way it shall be realised.This fact provides the reason for education including, essentially,two dimensions: culture-creating and political.Their specification, in the sphere of education, is naturallyorbiting around the openly or secretly suggested ideal of man andcitizen desired by a given society, or its particular group in power,influencing the process of defining educational aims and theirways of realisation.The reflections presented in this article do not aspire to exhaustthe entire issue of culture-creating and political dimensionof educational activity, but merely to bring out some, in our opinionimportant, traits. They also want to become an invitation tothe reflection upon education and challenges it faces in the contextof a broader debate over the shape of Poland in the processof democratisation, uniting Europe and the world exposed to theprocesses of globalisation.